The effect of low donor-to-recipient body weight ratio on graft survival after dual kidney transplantation from pediatric deceased donors - Mingchuan Huang; Shenghui Wu; Pengfei Gao; Li Zhou; Qian Fu; Chenglin Wu; Huanxi Zhang; Yitao Zheng; Xiaojun Su; Wenrui Wu; Jinghong Tan; Qiang Zhang; et al. (Renal Failure)
Background Dual kidney transplantation (DKT) from small pediatric donors, either en-bloc or split dual kidney transplantation, contributes to mitigating organ scarcity. This study investigates the prognosis of DKT from pediatric deceased donors, and influencing factors.Method A retrospective study included recipients who underwent DKT from pediatric donors between 2012 and 2022. Recipients were categorized into low mismatch (BWLM, n = 30) and high mismatch (BWHM, n = 10) groups based on donor-recipient weight ratio of 1:10. Outcome encompassed recipient and graft survival, renal function, and adverse events.Result Forty recipients were included. The average follow-up period was 54.6 months. The 1, 3, and 5-year patient survival were 97.4%, with no significant differences between en-bloc and split dual kidney transplantation or between BWLM and BWHM groups. The graft survival at 1, 3, and 5 years were 89.9%, the graft survival of BWHM group was lower than BWLM group (70% vs 96.7%, p = 0.039). The average eGFR at 1, 3, and 5 years postoperatively were (78.93 ± 25.23), (83.82 ± 32.4), and (85.92 ± 37.08) mL/min/1.73 m2, respectively. The BWHM group also experienced higher rates of graft-related surgical complications (p = 0.006) and urinary tract surgical complications (p = 0.042).Conclusion DKT from pediatric donors yields favorable outcomes, with similar graft survival and complication rates across surgical subgroups. However, significant donor-recipient weight mismatch, particularly when the ratio is less than 1:10, may contribute to increased surgical complications and poorer graft survival. Efforts to minimize extreme weight mismatch are recommended to optimize outcomes.